Influence of Migration and Plugging of Nanoparticles on Coal Permeability in Coal Reservoirs - Xiaopeng Zhai; Weihong Chen; Yun Xu; Yishan Lou; Shuhong Xu; Lihui Zheng; Zhiyang Guo; Yuanchang Chen; Hongyong Hao; Jianfang Jiang (Geofluids)
The plugging of nanopores in low-permeability coal reservoirs is an important factor that affects productivity reduction. However, the mechanism of plugging of the nanopores in coal reservoirs remains unclear. In this study, the coal samples from the Anze coalbed methane block of the North China Oilfield are used as the research object. Experiments are conducted on the mechanism of nanopore plugging by the variation of nanopore permeability based on the pressure oscillation method and the nanopore (scanning electron microscope) method. The research shows that the foreign working fluid invades a coal sample; the sample changes from being hydrophobic to being water absorbent within a certain period. The instability caused by the expansion of coal clay mineral particles promotes the dispersion and shedding of particles, and the migration of particles is accelerated under the shear stress of the working fluid. In addition, the viscosity and pressure difference of the working fluid are important factors that affect particle plugging. The viscosity of the fluid increased by two times, and permeability decreased by 1.21 times. As the pressure difference increases by two times, permeability can be reduced by up to two orders of magnitude. The findings of this study can help for better understanding of the mechanism of plugging of the nanopores in coal reservoirs and the reasons of production reduction in low-permeability coal reservoirs. Such findings provide theoretical support for the selection of the working fluid, and reasonable production pressure difference can effectively reduce the damage on coal permeability in a low-permeability coal reservoir.